The weekend effect in critically ill patients with severe infections in Japanese intensive care units: a multicenter retrospective cohort study - Teiko Kawahigashi; Taisuke Jo; Tetsuya Komuro; Jan De Waele; Liesbet De Bus; Akihiro Takaba; Akira Kuriyama; Atsuko Kobayashi; Chie Tanaka; Hideki Hashi; Hideki Hashimoto; Hiroshi Nashiki; et al. (Therapeutic Advances in Infectious Disease)
Background: Reduced or delayed access to medical resources on weekends could lead to worsening outcomes, in critically ill infected patients requiring intensive care unit (ICU) admission. Objective: To investigate the “weekend effect,” on critically ill infected patients in Japanese ICUs for the first time. Design: Multicenter retrospective cohort study. Methods: We examined data from Japanese ICU patients participating in the DIANA study, a multicenter international observational cohort study. This prospective investigation enrolled critically ill patients with infections admitted to the ICU. The primary endpoint was successful discharge from the ICU within 28 days of admission. Outcome measures were evaluated through both univariate and covariate Cox regression analyses, providing hazard ratios (HRs) along with estimated 95% confidence intervals (CIs). Results: Out of the 276 patients enrolled in the DIANA study across 31 facilities, 208 patients (75.4%) meeting the inclusion criteria were included in the analysis. The weekday ICU admission group comprised 156 patients (75.0%), while the weekend ICU admission group comprised 52 patients (25.0%). In the multivariate Cox regression analysis, there were no statistically significant differences observed in the rates of ICU discharge alive within 28 days and 14 days (28 days, HR: 0.94, 95% CI: 0.63–1.40; 14 days, HR: 0.97, 95% CI: 0.64–1.48). Furthermore, the overall ICU mortality rates at 28 days and 14 days after ICU admission did not show statistical significance between patients admitted on weekends and those admitted on weekdays (ICU mortality, 28 days: 13.5% vs 11.5%, p = 0.806; 14 days: 7.7% vs 10.9%, p = 0.604). Conclusion: The rates of ICU discharge alive within 28 days after ICU admission did not differ significantly between weekday and weekend admissions, both in the unadjusted and adjusted analyses. Moreover, further well-designed studies are warranted to thoroughly assess this effect.